The Effectiveness of Digital Technology in Increasing Interest in Learning Indonesian in Elementary Schools - Achmad Suherman (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This study is a qualitative study with a descriptive approach, namely an approach that aims to analyze each main object in this study using descriptive sentences. The main objects in this study include Digital Technology, Learning Interest, and Indonesian. The data used in this study is secondary data obtained indirectly through scientific articles, magazines, books, journals, and so on. The data mentioned by the researcher was analyzed through the stages of data collection, data reduction, data selection, and drawing conclusions. The conclusion in this article show interest can be fostered through enjoyment and in line with psychological development. In today's digital age, children's psychological development also coexists with digital technology. Children can enjoy watching cartoons on digital media, playing games, and so on. This enjoyment should be guided in the right direction, namely by learning Indonesian using digital technology. Teachers and students involved in the learning process will be encouraged to use digital technology systems if they believe they will benefit them. Learning activities and digital technological advancements are inseparable, although this can have both positive and detrimental impacts. For students to benefit from digital technological advancements, positive thinking is necessary.